Komunitas Ikan di Perairan Danau Wilayah Sulawesi Utara dan Gorontalo - Haryono, Haryono (Universitas Atma Jaya Yogyakarta, 2004)
The study of lake fishes community in North Sulawesi and Gorontalo provinces was done during July and August 2001. The lakes of study were Tondano (St.1), Moat (St.2), Tondok (St.3) and Limboto (St.4) under observation methods to determine the fishes diversity, abundance, local distribution, status and economy values. There were 17 different species from 12 families screened during this study, the Cyprinidae was the dominant one and consist of three species. Overall the variation of fishes consist of eight introducable species and nine native species. The most abundance species was Ophieleotris aporos and the most wide distributed was Cyprinus carpio, mostly species have economic values. Comparing to three other lakes, the Limboto has the most various species of fishes.